Application of theoretical model in normalization of vertical jump test results with respect to the body mass - Aleksandar Kukrić; Borko Petrović; Radenko Dobraš; Željko Sekulić; Igor Vučković (University of Banja Luka, Faculty of physical education and sport, 2017)
The aim of this study was to examine the efficiency of application of the theoretical model in normalization of motor ability tests in order to neutralize the influence of body mass on muscle strength during various vertical jumps. The sample of participants was consisted of 60 basketball players that play in positions of power forward and center. Independent variables were body mass, body height and body fat percentage, whereas dependent variables were divided into variables that directly and indirectly estimate muscle strength during various vertical jumps. The results of motor ability tests were normalized using a theoretical exponent b=0,67 for direct assessment of muscle strength, while exponent b=0 was used for indirect muscle strength assessment. Based on the obtained results it has been concluded that: 1) before the normalization of the vertical jump test results, there was a moderate positive correlation between the results of the direct muscle strength assessment and body mass (0,44; 0,38) and 2) a correlation between the tests of the indirect muscle strength assessment and body mass was inadequate (-0,09;-0,14). After the application of the theoretical model in normalization of results, it has been noted that correlation coefficients decrease between the tests of direct muscle strength assessment and body mass (-0,08;-0,14). Correlation coefficients in the indirect muscle strength assessment tests remained unchanged (-0,09;-0,14). In that way, we obtained muscle strength results in vertical jumps independently from the body mass.